The professional translator vs. Google Translate: the case of Lars Larsen’s autobiography - Anne Schjoldager; Kristine Bundgaard; Helle Dam Jensen; Tina Paulsen Christensen (Hermes, 2024)
The final version of the article will be uploaded as soon as possible.